2003
DOI: 10.1074/jbc.m308240200
|View full text |Cite
|
Sign up to set email alerts
|

RasGRP1 Represents a Novel Non-protein Kinase C Phorbol Ester Signaling Pathway in Mouse Epidermal Keratinocytes

Abstract: The mouse skin model of carcinogenesis has been instrumental in our appreciation of the multistage nature of carcinogenesis. In this system, tumor promotion is a critical step in the generation of tumors and is usually achieved by treatment with the phorbol ester 12-O-tetradecanoylphorbol-13-acetate (TPA). Although it is generally assumed that protein kinase C (PKC) is the sole receptor for TPA in this system, we sought to evaluate whether non-PKC pathways could also contribute to the effects of phorbol esters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 39 publications
0
52
1
1
Order By: Relevance
“…Similarly, 10 Amol/L GF109203X did not have any effect on Ras activation induced by 5-minute treatment with 1 Amol/L TPA. Nevertheless, as we have reported previously for TPA (10), acute activation of extracellular signal-regulated kinase (ERK) by bryostatin 1 was sensitive to PKC inhibition (data not shown).…”
Section: Bryostatin 1 Is Less Effective Than Tpa At Inducing Ras Actimentioning
confidence: 70%
See 3 more Smart Citations
“…Similarly, 10 Amol/L GF109203X did not have any effect on Ras activation induced by 5-minute treatment with 1 Amol/L TPA. Nevertheless, as we have reported previously for TPA (10), acute activation of extracellular signal-regulated kinase (ERK) by bryostatin 1 was sensitive to PKC inhibition (data not shown).…”
Section: Bryostatin 1 Is Less Effective Than Tpa At Inducing Ras Actimentioning
confidence: 70%
“…We have recently shown that the novel DAG receptor and Ras exchange factor RasGRP1 is expressed in mouse epidermal keratinocytes and mediates activation of Ras by TPA in a PKC-independent manner (10). The purpose of the work described here was to determine if bryostatin 1 could also modulate RasGRP1 in the mouse keratinocyte system and to compare its effects with those of TPA.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests the possible involvement of a calciumdependent Rac/Cdc42 GEF. Although calcium-regulated GEF for Ras, R-Ras and Rap-1 have been identified [49,50], a calcium-dependent Rac/Cdc42-GEF has not yet been described. Alternatively, the calcium-dependent phosphorylation of RhoGDIa leads to Rac membrane translocation and activation in PC3 human prostrate cells [51].…”
Section: Discussionmentioning
confidence: 99%